Ethnobotanical survey of medicinal plants used for pregnant women׳s health conditions in Menoua division-West Cameroon. (3rd February 2015) - Yemele, M.D.; Telefo, P.B.; Lienou, L.L.; Tagne, S.R.; Fodouop, C.S.P.; Goka, C.S.; Lemfack, M.C.; Moundipa, F.P.
Abstract: Ethnopharmacological relevance: In Cameroon, most women use traditional medicine for the treatment of pregnancy and childbirth complaints. In order to identify some of the medicinal plants locally used to alleviate these complaints, an ethnobotanical survey was undertaken in five villages of Menoua Division (West-Cameroon). Materials and methods: Interviews were conducted through structured questionnaires among 24 traditional healers and 179 women living either in the town of Dschang or in 4 neighboring villages. After having recorded the interviewee personal information on issues related to medicinal plants utilization, a literature investigation on their therapeutic or pharmacological effects and phytochemical composition was conducted. Results: A total of 88 medicinal plants species used to treat 24 conditions occurring during or after pregnancy and belonging to 70 genera or 34 families were recorded. Maximum medicinal uses of plants are reported for the treatment of the following ailments: swelling of legs and ankles (23%), facilitation of delivery (22%), cleaning of the baby (12%). Most herbal remedies are prepared with the leaves (30%), leaves+stems (28%) and whole plant (23%) as maceration (76%). The majority of women who used medicinal plants were very satisfied (75 %) and it is reported that most of these plants are used in the treatment of women health conditions. Conclusion: Many herbal remedies used for the treatment of pregnant women׳s health conditions in Menoua division-West Cameroon have been revealed. It would therefore be judicious for our government and research institution to evaluate the therapeutic and toxicological potentials of these plants in order to valorize their use. Graphical abstract: